PENERAPAN SAPTA PESONA DI OBJEK WISATA BENTENG FORT DE KOCK BUKITTINGGI - Rafi, Zeranita; Kasmita, Kasmita; Waryono, Waryono (Journal of Home Economics and Tourism, 2015)
This study aimed to describe the adoption of Sapta Pesona Attraction in Fort Fort De Kock Bukittinggi which includes seven indicators Sapta Pesona namely: safe, orderly, clean, cool, beautiful, friendly, and memories. This type of research is quantitative descriptive. This study population is the average monthly number is 8231 people. The number of samples in this study are numbered 99 people were taken by using the formula Riduwan. The sampling technique in this research is non probability sampling (purposive sampling). Data collection techniques using a questionnaire based on the Likert scale that has been tested for validity and reliability. The results showed that the overall application of stepping in attraction Fort Fort de Kock Bukittinggi classified in the category quite well with the average value score of 176.99 in the range of 160 - <200 with the interpretation of the percentage of 46.47%, while under each each indicator are: for safe, orderly, clean, friendly and reasonably good memories of the category and to cool and beautiful in both categories.Key Word: Application, Sapta Pesona, Tourist